2020
DOI: 10.1002/14651858.cd011024.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for increasing acceptance of local anaesthetic in children and adolescents having dental treatment

Abstract: Interventions for increasing acceptance of local anaesthetic in children and adolescents having dental treatment (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 88 publications
0
24
0
1
Order By: Relevance
“…Negative treatment experiences may trigger a vicious cycle, i.e., leading to avoidance of dental appointments and hindering more positive experiences to take place [3][4][5]. Furthermore, avoiding dental appointments may affect the oral health [3-5] jeopardizing the well-being of young patients with long-term consequences such as topical anesthesia, local anesthesia, or analgesics are still substandard [6][7][8]. The routines applied by Swedish dentists have shown that 'about 35% were more indifferent to their patient's experiences of pain and psychological management' [7].…”
Section: Introductionmentioning
confidence: 99%
“…Negative treatment experiences may trigger a vicious cycle, i.e., leading to avoidance of dental appointments and hindering more positive experiences to take place [3][4][5]. Furthermore, avoiding dental appointments may affect the oral health [3-5] jeopardizing the well-being of young patients with long-term consequences such as topical anesthesia, local anesthesia, or analgesics are still substandard [6][7][8]. The routines applied by Swedish dentists have shown that 'about 35% were more indifferent to their patient's experiences of pain and psychological management' [7].…”
Section: Introductionmentioning
confidence: 99%
“…Especially, children seem to be more vulnerable to pain associated with dental treatment. Some authors examine this issue and emphasize the importance of local anesthesia (LA) in achieving pain-free treatment [ 40 ]. However, according to the authors, anxiety and stress associated with local anesthetic injection makes pain-free treatment challenging [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preschool children differ in maturity within their age group regarding communication methods and abilities. In the acute dental situation, every child may experience a higher impact of anxiety, fear, and pain [19]. Medical conditions and/or functional variations may also prevent children from cooperating and coping with the acute dental situation [14].…”
Section: Preschool Childrenmentioning
confidence: 99%